Multiphase voltage-mode hysteretic controlled VRM with DSP control and novel current sharing - Abu-Qahouq, Jaber A.; Pongratananukul, N.; Batarseh, I.; Kasparis, Takis (My University, 2002)
Applying the voltage-mode hysteretic control to multiphase Voltage Regulator Modules (VRMs) can satisfy many of the new and future generation of microprocessors and ICs powering requirements. This is because of the numerous advantages that can be obtained when both techniques are used. However, several challenges arise that include current sharing, multiphase control signals distribution, high-speed comparators noise sensitivity, hysteretic band accuracy and stability, VRM operation startup, and the stability of the controller operation at large load transients. Addressing these challenges cannot be easily achieved using analog and discrete components but rather DSP can be used to solve these problems. In this paper, multiphase voltage-mode hysteretic controlled VRM with DSP control and novel current sharing is proposed. © 2002 IEEE.
Keywords: Inductors; Power supplies; Power generation; Regulators; Switching frequency; Power system transients; Microprocessors; Digital signal processing; Hysteresis; Voltage control